1-stage CoMT-CAMD: An approach for integrated design of ORC process and working fluid using PC-SAFT. (23rd February 2017) - Schilling, Johannes; Lampe, Matthias; Gross, Joachim; Bardow, André
Abstract: Organic Rankine Cycles (ORC) transform low-temperature heat into electrical power. To exploit the full potential of a low-temperature heat source, the ORC system is tailored to the specific application. Tailoring an ORC system is challenging, since both process and working fluid have to be optimized simultaneously. We present an approach for integrated design of ORC process and working fluid that enables tailoring an ORC process and the working fluid in a single optimization problem. This approach builds upon the continuous-molecular targeting – computer-aided molecular design (CoMT-CAMD) approach presented byLampe et al. (2015a) . Here, a detailed process model is combined with a modern model of the working fluid, the perturbed-chain statistical associating fluid theory (PC-SAFT) equation of state. A group contribution approach for PC-SAFT is integrated to allow the computer-aided molecular design (CAMD) of novel fluids within the optimization. In this work, we formulate the corresponding mixed integer nonlinear program (MINLP) problem and solve it in one stage by deterministic optimization combining CoMT and outer-approximation. We therefore call the approach 1-stage CoMT-CAMD. 1-stage CoMT-CAMD problems can be solved efficiently using commercial solvers enabling both single-objective and multi-objective optimization of process and working fluid. The presented approach is employed in two ORC case studies. The first case study outlines the applicability for single-objective and multi-objective optimization for combined heat and power generation. In the second case study, a detailed turbine model is considered within the optimization showing the possibility of modelling the process components in a more detailed manner. The 1-stage CoMT-CAMD approach thus efficiently solves complex integrated design problems based on a consistent thermodynamic picture. Abstract : Highlights: A framework for integrated design of ORC process and working fluid is proposed. Computer-aided molecular design enables to identify novel and promising fluids. The working fluids are modeled by the modern PC-SAFT equation of state. Detailed process models of ORC systems are considered. The framework enables single- and multi-objective optimization of the ORC system.